Clinicopathological study of postmenopausal bleeding in a tertiary hospital: a retrospective analysis - Gopalakrishna, Nandini; Fernandes, Jessica; Surjan, Prerna; Sonti, Shruthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Postmenopausal bleeding is bleeding from the genital tract one year after menopause. The incidence is 4-11%. It is one of the cardinal signs of endometrial carcinoma. There is 10% risk of genital cancer and 10% risk of significant pathology and needs evaluation. In majority of them, it is due to benign condition such as endometrial atrophy or polyp. The aim of the present study was to evaluate the endometrial thickness by transvaginal ultrasound and to correlate with the histopathological pattern of the material obtained by hysteroscopic guided biopsy or curettage. Methods: A retrospective analysis of all the patients attending the outpatient department from January 2017 to December 2019 was done. This study was undertaken at M.S. Ramaiah Medical College and Hospitals. All patients with postmenopausal bleeding were evaluated clinically, then they underwent PAP smear, transvaginal ultrasound for endometrial thickness. This was followed by hysteroscopic guided biopsy and curettage. The material obtained was sent for histopathological examination as it is the gold standard for further management. Results: A total of 89 patients were enrolled for the study. The final results revealed atrophic endometrium in 35.95%, hyperplasia without atypia in 20.2%, polyps in 11.2% and endometrial carcinoma in 6.7%. Conclusions: In postmenopausal bleeding assessing endometrial thickness by transvaginal ultrasound is ideal. Hysteroscopy is a simple technique to evaluate the uterine cavity and take biopsy for histopathological examination, which is the gold standard.